Research and development of Cordyceps in Taiwan - Ching-Peng Chiu; Tsong-Long Hwang; You Chan; Mohamed El-Shazly; Tung-Ying Wu; I-Wen Lo; Yu-Ming Hsu; Kuei-Hung Lai; Ming-Feng Hou; Shyng-Shiou Yuan; Fang-Rong Chang; Yang-Chang Wu (Food Science and Human Wellness)
Cordyceps is treasured entomopathogenic fungi that have been used as antitumor, immunomodulating, antioxidant, and pro-sexual agent. Cordyceps, also called DongChongXiaCao in Chinese, Yartsa Gunbu (Tibetan), means winter worm-summer grass. Natural Cordyceps sinensis with parasitic hosts is difficult to be collected and the recent findings on its potential pharmacological functions, resulted in skyrocketing prices. Therefore, finding a mass-production method or an alternative for C. sinensis products is a top-priority task. In this review, we describe current status of Cordyceps research and its recent developments in Taiwan. The content and pharmacological activities of four major industrial species of Cordyceps (C. sinensis, Cordyceps militaris, Cordyceps cicadae and Cordyceps sobolifera) used in Taiwan, were reviewed. Moreover, we highlighted the effect of using different methods of fermentation and production on the morphology and chemical content of Cordyceps sp. Finally, we summarized the bottle-necks and challenges facing Cordyceps research as well as we proposed future road map for Cordyceps industry in Taiwan.